A Gestalt Account of Lightness Illusions. (September 2014) - Gilchrist, Alan
Illusions of lightness offer valuable clues to how lightness values are computed by the visual system. The traditional domain of lightness illusions must be expanded to include failures of constancy, as there is no distinction between these categories. Just as lightness is (relatively) constant in the face of changes in illumination level, so it is equally constant in the face of changes in background reflectance. Simultaneous lightness contrast, the most familiar lightness illusion, is fairly weak, and represents a failure of background-independent lightness constancy. It is argued that a combination of the highest-luminance rule of anchoring plus the Kardos idea of codetermination can account for most lightness illusions. Kardos suggested that the lightness value of a target surface is partly determined relative to the field of illumination (or framework) in which it is embedded, and partly relative to the neighboring field of illumination. Although Kardos did not apply his principle of codetermination to failures of background-independent constancy such as the simultaneous contrast illusion, this can be done rather easily by defining a framework as a perceptual group instead of identifying it strictly with an objective field of illumination.